THE EFFECT OF DEPRESSION ON REAL AND IDEAL SELF-STEEM: A STUDY WITH THE IRAP (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study aimed to compare the relational responses of actual and ideal self-esteem through the Implicit Relational Assessment Procedure (IRAP) and to explore the correlation between the participants' scores on the Rosenberg Self-Esteem Scale (RSS) and the D-IRAP scores. Twenty adults participated in the study, distributed in two groups, with and without depression. The procedure had two phases: (a) application of BDI-II and RSS, (b) application of IRAP actual self-esteem, and IRAP ideal self-esteem. The results showed that participants with depression differed from participants without depression in terms of self-esteem assessed by the RSS and showed similarities regarding that evaluated by the IRAP. Participants with depression showed: negative actual self-esteem bias and positive ideal self-esteem bias. Participants without depression showed no differences in actual and ideal self-esteem.
Keywords: IRAP; Self-esteem; Depression; implicit attitudes; Relational responding